2005
DOI: 10.1074/jbc.m408658200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Secretory Granule-targeting Efficiency by Cis and Trans Compounding of Sorting Signals

Abstract: Several protein domains acting through seemingly different mechanisms have been reported to have the capacity to target proteins to dense core secretory granules. Because proteins enter secretory granules with different efficiencies and because some of these proteins contain more than one granule-targeting motif, we have investigated whether compounding sorting signals could alter the efficiency of protein entry into secretory granules. In the current study we demonstrate that a paired basic cleavage site from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Our results indicate that both motifs may constitute proglucagon sorting signals, and that they may act independently; mutating the dibasic site does not affect alpha-helical content, and altering the helical content leaves the dibasic site intact (Guizzetti and Dhanvantari 2012, unpublished observations). It has been shown that multiple types of sorting signals increase the efficiency of sorting to granules (Lacombe et al 2005), which may then translate into a greater degree of physiological regulation of secretion. In this regard, the sorting efficiency of proglucagon may be similar to that of proinsulin, which also contains a number of different sorting signals (hexamerisation, CPE binding sites and dibasic sites).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that both motifs may constitute proglucagon sorting signals, and that they may act independently; mutating the dibasic site does not affect alpha-helical content, and altering the helical content leaves the dibasic site intact (Guizzetti and Dhanvantari 2012, unpublished observations). It has been shown that multiple types of sorting signals increase the efficiency of sorting to granules (Lacombe et al 2005), which may then translate into a greater degree of physiological regulation of secretion. In this regard, the sorting efficiency of proglucagon may be similar to that of proinsulin, which also contains a number of different sorting signals (hexamerisation, CPE binding sites and dibasic sites).…”
Section: Discussionmentioning
confidence: 99%
“…Although no consensus secretory granule-sorting sequence has emerged from these studies, various structural motifs influencing targeting of proteins to secretory granules have been identified. These motifs include hydrophobic disulfide-bonded loop structures found in a variety of regulated secretory proteins such as pro-opiomelanocortin, CgA, and CgB (15,28,32,33); amphipathic ␣-helical domains that mediate interaction with membranes (15,34,35); and Ca 2ϩ -binding domains that promote protein aggregation prior to sorting (36,37). Several studies on the secretory prohormone CgA have suggested a direct correlation between the sorting process and the formation of secretory granules (9 -13).…”
Section: Discussionmentioning
confidence: 99%
“…11), but the search for sequence similarity with other proteins by BLAST (Basic Local Alignment Search Tool) and PSI-BLAST (Position-specific Iterative-BLAST) did not reveal homology below the threshold of significance E ϭ 0.01. ␣-Helical domains with amphipathic properties have been suggested to mediate targeting of several prohormones into the regulated pathway, for instance CgA (13), prosomatostatin (14), and PCs (15,16), possibly by virtue of interaction with membrane components (5,43). In support of this concept, we show that ␣-helix-containing domains SgII- (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) and SgII-(333-348) function as transferable DCG-sorting signals; the hydrophobic "faces" of these two amphipathic helical segments in cis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting-for-entry proposes that a structural/conformational motif within an aggregate of secretory proteins mediates subsequent association to a protein receptor or a lipid component of the membrane of the trans-Golgi network (TGN). The quest for identifying a consensus sorting signal has proven elusive, and it now appears that such process may rather depend on a variety of motifs (5-7), including hydrophobic disulfide-bonded loop structures (8 -12) or amphipathic ␣-helices (13)(14)(15)(16). In the sorting-by-retention model, selective aggregation/condensation occurs in post-TGN immature secretory granules (ISGs), resulting in retention of regulated secretory proteins, whereas nonaggregated proteins are removed into constitutive-like secretory vesicles (3).…”
mentioning
confidence: 99%